The impact of easy and early access to old-age benefits on exits from the labour market: A macro-micro analysis - Ewa Gałecka-Burdziak; Marek Góra (IZA Journal of European Labor Studies, 2016)
We examine whether easy and early access to old-age benefits induce older workers to become inactive. We use Polish LFS data. We find added worker effect prevailing over discouraged worker effect. The latter arises after a few quarters and is asymmetric. Females permanently leave the workforce. More males leave the workforce in contractions than re-enter in expansions. If old-age benefit becomes the main source of income, the worker (after 1 year) is 8 to 20 times more likely to exit the market than unemployment or social welfare beneficiaries. Our findings support higher retirement age-the age when workers become eligible for old-age benefits.
Keywords: J14; J22; 330; Old-age benefits; Discouraged workers; Discouraged worker effect; Unemployment outflow; Inflow to inactivity